Analisis Pengaruh Ukuran Komite Audit Dan Keberagaman Gender Komite Terhadap Kualitas Pelaporan Keuangan Di Sektor Transportasi Dan Logistik - Rosita Dewi; Rahman Ansari; Muhammad Iqbal Pribadi (CV. ITTC INDONESIA, 2025)
In 2018, PT Garuda Indonesia was involved in a financial statement manipulation scandal that affected investor confidence in the Indonesian capital market. The actions were indicated as window dressing. Based on POJK No. 39/POJK03/2019/Regarding SAF Commercial Banks, window dressing refers to the manipulation of financial statements with the aim of presenting the company's financial condition in a more favorable light than the actual reality. This study uses a quantitative approach with secondary data collected through documentation techniques. The sample was determined using purposive sampling, comprising 158 data samples. Analysis was conducted using classical assumption tests, multiple linear regression tests, hypothesis tests, and coefficient of determination tests. The results of the study indicate that the size of the audit committee has a significant effect on financial reporting quality, while gender diversity in the committee does not have a significant effect on financial reporting quality.